The Effect of Using Frontloading Strategy on Students' Vocabulary Mastery at the Eleventh Grade of SMA Negeri 1 Angkola Selatan In 2021/2022 Academic Year - Evi Sitohang (JURNAL LINER (Language Intelligence and Educational Research), 2022)
ABSTRACT: The objectives of this research was to find out: 1) the extent of using frontloading strategy in teaching vocabulary mastery at the eleventh grade studentsof SMA Negeri 1 Angkola Selatan in 2021/2022 academic year. 2). the extent of the students’ vocabulary mastery before and after using frontloading strategy on students’ vocabulary mastery at theeleventh grade studentsofSMA Negeri 1 Angkola Selatan in 2021/2022 Academic Year. 3) whether there is any significant effect of using frontloading strategy on students’ vocabulary mastery at theeleventh grade studentsofSMA Negeri 1 Angkola Selatan in 2021/2022 Academic Year. The population of this research were all theeleventh grade studentsofSMA Negeri 1 Angkola Selatan, totaling 130 students. The research sample was theeleventhMIA1students, which consist of 34 students who were taken by purposivesampling. The data collection technique used the observation sheet and test. The results of this research: 1) The application of frontloading strategy was 3.8,it was categorized “very good” criterion. 2) The mean score of the students’ vocabulary mastery before using frontloading strategy was 39 it was categorized “fail”. Meanwhile, after using frontloading strategy was 83 it was categorized “verygood”. 3) the results of data analysis showed that the ttest is higher than ttable (ttest 14.5> ttable 2.03). So, the hypothesis was accepted. Its mean that there is a significant effect of frontloading strategy on students’ vocabulary mastery at the eleventh grade studentsofSMA Negeri 1 Angkola Selatan in 2021/2022 academic year. Keywords:Frontloading Strategy, Vocabulary Mastery ABSTRAK:Tujuan penelitian ini adalah untuk mengetahui: 1) sejauh mana penggunaan frontloading strategy dalam pengajaran kosakata pada siswa kelas sebelas SMA Negeri 1 Angkola Selatan Tahun Pelajaran 2021/2022. 2) sejauh mana penguasaan kosakata siswa sebelum dan sesudah menggunakan frontloading strategy pada kelas sebelas SMA Negeri 1 Angkola Selatan Tahun Pelajaran 2021/2022. 3)Untuk mengetahui apakah ada pengaruh yang signifikan penggunaan frontloading strategy terhadap penguasaan kosakata pada siswa kelas sebelas SMA Negeri 1 Angkola Selatan Tahun Pelajaran 2021/2022. Populasi dalam penelitian ini adalah seluruh kelas sebelas SMA Negeri 1 Angkola Selatan yang berjumlah 130siswa. Sampel penelitian ini adalah siswa kelas sebelas MIA 1 yang berjumlah 34siswa yang diambil secara purposivesampling. Teknik pengumpulan data menggunakan lembar observasi dan tes. Hasil penelitian ini: 1) Penerapan strategy frontloading adalah 3.8, termasuk kriteria “sangat baik”. 2) Rata rata skor penguasaan kosakata siswa sebelum menggunakan strategi frontloading adalah 39 dikategorikan “gagal”. Sedangkan setelah menggunakanstrategi frontloading adalah 83 dikategorikan “sangat baik”. 3) hasil analisis data menunjukkan bahwa thitung lebih besar dari ttabel (thitung 14.5> ttabel 2,03). Jadi, hipotesis diterima. Artinya ada pengaruh yang signifikan strategi frontloading terhadap penguasaan kosakata siswa pada siswa kelas sebelas SMA Negeri 1 Angkola Selatan tahun ajaran 2021/2022 Kata Kunci:Frontloading Strategy , Vocabulary Mastery